PENGARUH NIKOTIN TERHADAP KELAINAN TULANG DAN ORGAN INTERNAL MENCIT (Mus musculus) - Pieter Kakisina; Win Darmanto; Bambang Poernomo (The East Java Biological Society, 2004)
This study was designed to identify the effects of nicotine on the skeletal and internal organ abnormalities of mice prenatally. Seventy two female mice strain Balb/C were used. Pregnant mice on gestation days (GD) 8, 10, and 12 was injected intraperitoneally with 3, 6, and 12 mg/kg BW nicotine respectively. Control nice was injected by aguabidestylata. On GD 18, and all of pregnant mice were sacrificed, and a half of living fetuses were immersed in Bouin’s solution to observe their internal organs, while another half were immersed in 95% ethanol to observed sekeletal malformation using alizarin red S staining. Results were analyzed using SPSS program version 11 for personal computer.The results showed that nicotine caused Skeletal malformation, especially in the sternum when administered on GD 8 and 10, in doses of 3 and 6 mg/kg BW, delayed of ossification was observed in the supraoccipital and sacrocaudal bones on GD 10 and 12 and doses of 12 mg/kg BW, while in the extremitas the malformation was observed in the proximal and medial phalanx both in the fore and hind limb especially on GD 10 and 12, and doses of 6 and 12 mg/kg BW. Nicotine was effects on the brain development especially hydrocephalus was observed on GD 8 and doses 10 and 12 mg/kg BW. Another internal malformation such as ectopic renalis was observed on GD 8 and doses of 3 and 6 mg/kg BW. These finding suggested that nicotine has caused skeletal malformation, brain malformatin and ectopic renalis, when administered in mice prenatally.